2005
DOI: 10.1182/blood-2004-09-3645
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF/HER-1 signaling in bone marrow mesenchymal stem cells: inducing cell expansion and reversibly preventing multilineage differentiation

Abstract: Epidermal growth factor receptor-1 (EGFR-1/ HER-1/ErbB-1) regulates proliferation and cell fate during epidermal development. HER-1 is activated by several EGF-family ligands including heparin-binding epidermal growth factor-like growth factor (HB-EGF), a mitogenic and chemotactic molecule that participates in tissue repair, tumor growth, and other tissue-modeling phenomena, such as angiogenesis and fibrogenesis. We found that mesenchymal stem cells (MSCs), the precursors of different mesenchymal tissues with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
172
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(188 citation statements)
references
References 39 publications
13
172
0
3
Order By: Relevance
“…3-(4,5-Dimethyl-thiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was applied to assess the effects of ion channel blockers on cell proliferation (19). Mouse MSCs were plated into 96-well plates at a density of 5 ϫ 10 4 cells per well in 200 l complete culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…3-(4,5-Dimethyl-thiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was applied to assess the effects of ion channel blockers on cell proliferation (19). Mouse MSCs were plated into 96-well plates at a density of 5 ϫ 10 4 cells per well in 200 l complete culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…71 Another pathway involved in pericyte recruitment is through heparin-binding epidermal growth factor (HB-EGF). 72 HB-EGF, implicated in cardiovascular development, has also been found to have protective effect on pericytes by supporting pericyte proliferation and minimizing the effects anoxiainduced apoptosis. 73 Several studies have demonstrated that HB-EGF pathways may experience crosstalk with PDGF pathways.…”
Section: Pericytes Mscs and Vascularizationmentioning
confidence: 99%
“…These signals promote migration, adhesion, proliferation, and survival in various cell types [13,15,16]. Both EGFR expression and EGF responsiveness have been reported in marrow-derived MSC [17][18][19][20][21]. We recently reported that stimulation of MSC with soluble EGF induces EGFR signaling and promotes MSC proliferation and migration without affecting pluripotency [18].…”
Section: Introductionmentioning
confidence: 99%